Effect of Storage on Quality of Stone Apple Ready-to-Serve Beverage - Rayaguru, Kalpana; Khan, Md. K; Sahoo, N R (Journal of Agricultural Engineering, 2008)
The present study is an effort to explore the possibility of effective utilization of the raw stone apple (Aegle marmelos correa), an indigenous fruit rich in nutritional as well as medicinal qualities. As the keeping quality of the whole fruit is very less, improvement in the post harvest processing and other relevant aspects need to be studied. Value added nutraceutical ready-to-serve (RTS) have been prepared. The process parameters have been standardized with respect to biochemical, microbial and sensory acceptance. Storage experiments for RTS with treatments (control, preservative and ginger) were conducted for 8 months and quality analysis was carried out to assess the storability. The ready to serve beverage with 13% pulp, 14Brix and 0.3% acidity was considered standard based on organoleptic evaluation. The RTS blended with ginger juice fetched higher sensory acceptability. Five hundred numbers of bottles of RTS of 200 ml. capacity each could be prepared from 25 kg of stone apple. During storage of the beverage all the biochemical qualities changed with storage period irrespective of the treatments. The total sugar, pH and ascorbic acid of the RTS got reduced with storage period where as an increasing trend was observed in acidity and TSS. However, the changes were maximum in control samples. The results suggest the use of ginger juice as a source of natural preservative. After four months of storage, there was an indication of presence of total mould count and total bacterial count in the stored samples, but the population was well within the safe limits till the end of a storage period of eight months.